(untitled) (Research, Society and Development, 2020)
This research evaluates the fungitoxic in vitro and in vivo effects of palmarosa essential oil (Cymbopogon martinii) on phytopathogenic fungi that infect soybean culture. In the in vitro test, the fungi were grown in PDA culture medium supplemented with pure essential oil in different concentrations (0.0125; 0.025; 0.05; 0.1; and 0.2%), the negative control (0%), and positive control (commercial fungicide Thiram 1 mL-1). The plates were inoculated with the fungi Phomopsis sp., Fusarium solani, Sclerotium rolfsii, and Macrophomina phaseolina. All plates were incubated for seven days at 27±2°C. In the in vivo test, soybean seeds were immersed in solutions with different palmarosa essential oil concentrations (0.05; 0.1; 0.2; 1.0; and 5.0%). After treatment, the seeds were artificially infected with the fungi under study, through contact with fungal colonies for 24 hours. The seeds were submitted to the sanity test and evaluated individually, using a stereoscopic microscope. Under in vitro conditions, the essential oil in concentrations from 0.05 to 0.1% precluded all studied fungi’ growth. In the in vivo test, the treatments with concentrations of 1% and 5% reduced the percentage of seeds infected by S. rolfsii, M. phaseolina e Phomopsis sp. but were unsuccessful against F. solani. The essential oil of palmarosa is a promising alternative to the use of conventional fungicides in soybean seeds.